Toxic Epidermal Necrolysis induced by Phenytoin: A Case Study - M, Manoj Kumar; M, Yogendra; M, Karthik; B, Gowthami; R, Yogananda; DR, Bharathi (Indian Journal of Pharmacy Practice)
Toxic epidermal necrolysis (TEN) is severe adverse cutaneous drug reaction that predominantly involves the skin and mucous membranes. It is usually induced by medications. Anti-convulsants such as phenytoin, carbamazepine and phenobarbital have been enlisted as high risk drugs for causing TEN. Objectives: The main objective of this case report is to evaluate the importance of detection, assessment and reporting of an adverse drug reaction and to improve the medication adherence. Methods: This is an observational type of case report which we observed in our hospital on regular ward rounds. Results: This is a case report of Toxic epidermal necrolysis due to a Phenytoin which was used in the treatment of epilepsy in a 25 year old female patient. Causality assessment of the event with Naranjo’ scale suggest “Probable”. Conclusion: Proper counselling to the patient regarding the use of medications is of utmost importance, in such life threatening conditions where treatment guidelines remain hazy.
Keywords: Adverse drug reaction; Toxic epidermal necrolysis; Phenytoin